Najnowsze rekomendacje Europejskiego Komitetu Zapobiegania Torturom w zakresie wykonywania kary pozbawienia wolności - Polak-Kruszyk, Aleksandra (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The protection of persons deprived of their liberty from torture and other forms of inhuman or degrading treatment or punishment has been strengthened by non-judicial means of a preventive character based on visits. The European Committee for the Prevention of Torture and Inhuman or Degrading Treatment or Punishment (CPT) is an essential element of that preventive mechanisms and it organizes direct visits in the member states of the Council of Europe. The CPT delegations have unlimited access to places of detention (prisons, juvenile detention centres, police stations, holding centres for immigration detainees, psychiatric hospitals, social care homes, etc.) and the right to move inside such places without restriction. Reports on country visits, as well as the Committee’s annual general reports on its activities, are the main source of the European standards on the treatment of persons deprived of their liberty. This article presents the latest recommendations of the European Committee for the Prevention of Torture regarding prisoners and prison conditions developed by the CPT in recent years. The first part of the analysis de-scribes the recommendations resulting from the reports to the Polish Government on the visits to Poland concerning the execution of the penalty of deprivation of liberty, carried out by the CPT in 2017 and 2022. Further part of the article includes the analysis of the 31st General Report on the CPT’s activities, where the problem of prison overcrowding in member states were underlined.
Keywords: European Committee for the Prevention of Torture and Inhuman or Degrading Treatment or Punishment; the CPT; the execution of the penalty of deprivation of liberty; the CPT standards; prison overcrowding